2017
DOI: 10.1007/s13205-017-0961-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biological applications of mycosynthesized silver nanoparticles

Abstract: Silver nanoparticles (AgNPs) have been known for their inhibitory and bactericidal effects. In the present study, less toxic AgNPs using is reported for the first time. The obtained AgNPs were characterized using UV-Visible spectrophotometer, XRD, FT-IR, FE-SEM with EDAX and HR-TEM. AgNPs showed the maximum absorbance at 420-430 nm. The transmission electron micrograph revealed the formation of considerably uniform-sized AgNPs with an average size of 20-50 nm. The reducing and capping agents responsible for Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…El-Naggar et al [19] prepared phycocyanin-reduced AgNPs that had an IC 50 value of 27.79 ± 2.3 µg/mL against mammary gland breast cancer (MCF-7), 31.78 ± 2.2 µg/mL against human lung fibroblast (WI38) cell line, and 32.97 ± 1.7 µg/mL against human amnion (WISH) cell lines. Similarly, Anbazhagan et al [50] synthesized AgNPs using Cunninghamella echinulata and tested their cytotoxicity against Vero cell lines, which showed an IC 50 value of 62.8 µg/mL for AgNPs. This activity was contrasted against the cytotoxic activity of AgNO 3 , which indicated that myco-synthesized nanoparticles were less cytotoxic to normal cells than bulk salts.…”
Section: Resultsmentioning
confidence: 99%
“…El-Naggar et al [19] prepared phycocyanin-reduced AgNPs that had an IC 50 value of 27.79 ± 2.3 µg/mL against mammary gland breast cancer (MCF-7), 31.78 ± 2.2 µg/mL against human lung fibroblast (WI38) cell line, and 32.97 ± 1.7 µg/mL against human amnion (WISH) cell lines. Similarly, Anbazhagan et al [50] synthesized AgNPs using Cunninghamella echinulata and tested their cytotoxicity against Vero cell lines, which showed an IC 50 value of 62.8 µg/mL for AgNPs. This activity was contrasted against the cytotoxic activity of AgNO 3 , which indicated that myco-synthesized nanoparticles were less cytotoxic to normal cells than bulk salts.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of brown color and absorbance units increases with the increase of the incubation period. Therefore, 15 min was used for the synthesis of biogenic AgNPs, providing an easy way and rapid protocol, which was an important advantage of biological methods compared to other methods using different primary biological material because they are normally synthesized within 30 min or more 21,22,[34][35][36][37] . TEM showed a widespread www.nature.com/scientificreports/ distribution of biogenic AgNPs with spherical and quasi-spherical shapes.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies and reports that plant extract NPs have strong antimicrobial activity. These AgNPs were effective in killing a range of bacterial pathogens involved in different infectious diseases, e.g., S. aureus, P. aeruginosa, E. coli and C. albicans are related to most common hospital-acquired infections 36,42 . Our biogenic AgNPs possessed higher antimicrobial activity than other biogenic AgNPs 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Metallic NPs consisting of one metal, metal oxides or a composite of several metals play a significant role in nanotechnology due to their potential utilization in industry and medicine [3][4][5][6][7]. NPs of noble metals possess low cytotoxicity, enable easy modification of their surfaces, have straightforward synthesis processes and excellent biocompatibility [8][9][10]. Such advantages make metallic NPs obtained by green synthesis (gNPs) prospective for applications in biological analysis, drug delivery and imaging, environmental monitoring, industrial catalysis and electronic devices [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many plants [11,12,21,[24][25][26], algae [4], microorganisms [1,3,[7][8][9][10]14,18,23,[27][28][29][30], as well as redox-imbalanced mammalian cells and systems [31] are known to produce nanostructured mineral crystals and metallic NPs with properties similar to chemically-synthesized materials. Biological agents, including polysaccharides, polypeptides, DNA, enzymes secreted by cells [24,[32][33][34][35][36][37][38][39][40][41] and purified enzymes [42,43] are able to reduce noble metal ions to gain metallic NPs.…”
Section: Introductionmentioning
confidence: 99%